Three-dimensional (3D) reconstruction of ultrasound foetal images using visualisation toolkit (VTK) / Grace Anabela Henry Dusim - Grace Anabela , Henry Dusim (2020)
Three-dimensional (3D) reconstruction of two-dimensional (2D) ultrasound images has been used for easier analysing of anatomy related to abnormalities. 3D image reconstruction is required as it helps doctors interpret results and assess any defects quickly. Not only does it improve the accuracy of diagnosis, but it also saves a lot of time. In this thesis, 295 slices of 2D ultrasound images of a foetal are used to do 3D reconstruction using surface rendering, volume rendering, and multiplanar rendering technique. A similar software known as 3D Slicer is also used to reconstruct the ultrasound image for comparison purpose. VTK can easily reconstruct the ultrasound image into a 3D image. It also allows for the measurement of foetal biometry, hence, reducing the risk of measurement inaccuracy. Other than that, multiplanar rendering allows the operator to view the 3D image in multiple planes without having to mentally imagine the plane as what has been done in a 2D ultrasound. In conclusion, VTK can clearly and accurately reconstruct a 3D image as well as measuring the length between two points. This software can help a lot of physicians in assessing any foetal abnormalities faster and accurately.